HUBUNGAN TINGKAT PENGETAHUAN ATLET FUTSAL TENTANG PERTOLONGAN PERTAMA SAAT MENGALAMI CEDERA SPRAIN DI LAPANGAN FUTSAL NOVEGA PIPIT - Fauzan Baso, Mohamad; Rahman, Abdul; Harry L Situmorang, Benny (Universitas Kadiri, 2023)
The knowledge level of futsal athletes in first aid is preparedness to prevent accidents to ligaments (sprain). The purpose of the research was to analyze the correlation between the knowledge of futsal athletes and first aid when suffering a sprain injury at the Novega Pipit futsal field. This research is quantitative using an analytic design with a cross-sectional approach. The total sample was 45 respondents taken by total sampling technique. The level of knowledge in this research was obtained through measurement using a first aid questionnaire tool on the sprain. Data analysis by using the chi-square test. The results showed that of the 45 respondents, about 19 respondents (42.2%) had good knowledge, and 13 respondents (28.9%). had sufficient knowledge and poor knowledge in the same results. about 27 respondents (60.0%) werewere ready for first aid injuries amounted to and 18 respondents (40.00%) was not ready for first aid injuries. The results of the chi-square test obtained a p-value = 0.003 <0.05. The conclusion mentioned that there is a correlation between the knowledge of futsal athletes about first aid when suffering a sprain injury at Novega Pipit Futsal Field.